Mass drug administration approved and candidate anthelmintics beginning on larval stage 1 Caenorhabditis elegans are generally potent, suggesting a novel, pre-infective control for helminths - Sam A. Attalla; Kathryn J. Isaac; Morgan Pfeffer; Justin R. Hockaday; Raegan Weatherly; Malia B. Asselin; Allison K. Lewis; Viveke Rai; William A. Huff Jr; Mason H. Long; Tashna Placide; Kala R. Pearce; et al. (PLoS ONE, 2026)
About 1.5 billion people are infected with at least one of three soil-transmitted helminths (STHs) — roundworm, hookworm, and whipworm— which have devastating outcomes for growth, nutrition, cognition, and school attendance, trapping them in poverty. The WHO currently approves only two anthelmintics with only one mechanism of action for mass drug administration (MDA), and resistance has been documented. This calls for new drugs and new strategies to reduce worm burden. Previous research, beginning with larval stage 4 (L4) C. elegans as a model, used a health-rating system to score individual worms in varying concentrations of anthelmintics. We hypothesized that younger worms would be more susceptible to drugs. We tested beginning at larval stage 1 (L1) C. elegans , using the health-rating system, with the same drugs, and additionally tested mebendazole, from both the L1 and L4 stages, allowing comparison at different stages. We found that L1 worms are susceptible to all anthelmintics tested, including the MDA drug of choice, albendazole, but surprisingly showed significantly lower efficacy with pyrantel and nitazoxanide at the L1 stage, as measured by motility and fraction alive, compared to L4. Furthermore, mortality and inhibition tended to begin earlier in the L4 stages. Finally, we found that ivermectin was the most potent anthelmintic against L1, as previously shown for L4. Beyond providing systematic drug-to-drug and stage-to-stage comparisons that can guide therapeutic development for larval-stage helminth infections, our findings suggest, for the first time, the possibility of spraying the environment with anthelmintics to reduce hookworm populations before people become infected. As hookworm is not infective until the L3 stage from soil, targeting L1-L3 larvae presents a strategic intervention window. Because previous work on C. elegans showed lower benzimidazole drug susceptibility than helminths, our L1 results may represent conservative estimates of efficacy against STH larvae in vitro and in environmental applications.